The Use of the Wordwall Application to Improve the Mastery of Thaharah Material for Grade IV Students at UPTD SDN 15 Parepare - Syarifah Asliah; Hamdanah; Buhaerah; Sitti Jamilah Amin; Firman (Ta'dib, 2025)
This study aims to examine the effectiveness of the Wordwall application as an interactive gamified medium in enhancing fourth-grade elementary school students' mastery of thaharah material in Islamic Religious Education at UPTD SDN 15 Parepare. Employing a quantitative experimental approach with a one-group pretest-posttest design, the research involved 26 students as participants. Data were collected through pretest and posttest instruments to measure conceptual understanding and practical application of thaharah, supplemented by observation sheets to assess student engagement during three learning sessions. Data analysis included descriptive statistics, normality testing, paired sample t-tests (both two-tailed and one-tailed), and N-Gain calculations. The results revealed a significant improvement in mastery, with the mean score increasing from 58.92 in the pretest to 90.46 in the posttest, supported by a paired t-test value of 10.261 and a significance level of 0.000 (< 0.05). The average N-Gain score of 0.72 indicated high improvement, while observation data showed effectiveness rising from 57% (sufficient) to 93% (very good). These findings demonstrate that Wordwall significantly enhances cognitive mastery, motivation, and active participation, aligning with Piaget's constructivism theory and Mayer's Cognitive Theory of Multimedia Learning. This study fills a research gap by providing empirical evidence on Wordwall's effectiveness in elementary-level thaharah instruction through face-to-face learning. Despite its contributions, limitations include a small sample and lack of a control group, suggesting the need for future research with broader samples and more comprehensive designs.